(untitled) (CIPEEX, 2024)
Bond failures between orthodontic devices and dental enamel are frequent and occur more frequently in posterior teeth. An additional layer of orthodontic adhesive at the interface between the tooth and the occlusal surface of the device seems to be a promising maneuver, but the results are controversial. The aim of this study was to compare the shear bond strength (SBS) of orthodontic tubes bonded to dental enamel following three different protocols. Forty-five bovine incisors were randomly divided into three groups: Group 1 – Transbond XT without reinforcement (control group); Group 2 – Transbond XT + reinforcement with Grandioso Heavy Flow flowable resin; Group 3 – Transbond XT + reinforcement with Forma conventional resin. The specimens were subjected to shear testing using a universal testing machine with a knife-blade tip and a 0.5 mm/min speed. The force required for shearing was greater in Group 2 when compared to Group 1. There was no statistically significant difference when comparing Groups 1 and 3, or 2 and 3. RUC was greater in Group 2 when compared to Group 1. Reinforcement with flowable resin increases RUC when compared to conventional bonding.